Adoption of Climate Smart Agricultural Practices in Punjab (Pakistan) (Journal of Asian Development Studies, 2024)
Pakistan is a vulnerable country in terms of both climate change and food security. With respect to food security, climate change can potentially affect crop production and access to affordable food. This research examined the adoption of Climate Smart Agriculture (CSA) through five key practices: i) balanced use of chemicals, ii) integrated pest management, iii) formal irrigation techniques, iv) knowledge of climate smart varieties, and v) change in crop calendar. The adoption of these CSA practices is assessed for farmers of wheat (a major crop in the food basket of Pakistan). The determinants of adoption were estimated using the Probit model. With the help of Data Envelopment Analysis (DEA) farm efficiency (technical) is calculated employing the survey of 384 farmers from Punjab. The results of the study suggest that only 17.4 percent of the farmers are adopters of CSA practices. The determinants, like farmer education, income, land ownership, etc., have a positive impact on adoption. Whereas age, land use, and distance from nearby city centers have negative associations with adoption. Based on the results and outcomes of the study, CSA practices are critical and hold the key to improving food security in the country. Adoption of CSA practices can help in attenuating the vulnerabilities of farmers to climate change.